Gender similarity and gender differnece of male and female athletes in cyclic sports - Tarasevich, O.; Mulyk, V.; Grashchenkova, Z.; Okun, D. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to determine the gender characteristics of male and female athletes specializing in cyclic sports. Material and Methods: the study involved 115 students and female students aged 17 - 23 years who are engaged in cyclic sports and have different sports qualifications. Of these, 54 female athletes and 61 male athletes. Research methods used: analysis and generalization of literary sources and Internet resources on the investigated problem; psychological methods: S. Bam`s "Masculinity / Femininity" methodology and the 16-factor Kettell questionnaire; methods of mathematical statistics. Results: the group of cyclic sports from the point of view of their influence on the formation of gender identity was examined, and gender similarities and gender differences among male and female athletes were identified who are involved in running athletics, swimming, cycling, skiing, short track, and rowing. Among the investigared athletes, the percentage ratio of masculine (48% of boys, 54% of girls) and androgynous (52% of boys, 46% of girls) personalities was revealed. Feminine personalities have not been identified. Most masculinization of athletes contributes to swimming (67%) and cross-country skiing (55%). The similarities and differences between masculine and androgynous girls and boys engaged in cyclic sports in relation to their personal qualities. Conclusions: the obtained results indicate the different level of personal qualities in both male and female athletes of the masculine and androgynous types. Young men showed the greatest differences in terms of such personal qualities as: subordination - dominance (t = 5.38; p <0.001) and restraint - expressiveness (t = 5.63; p <0.001) in favor of masculine-type male athletes. For girls, the most significant reliability was obtained by indicators: restraint - expressiveness (t = 4.89; p <0.001), timidity - courage (t = 5.19; p <0.001), self-confidence - anxiety (t = 6.17 ; p <0.001) and conservatism - radicalism (t = 5.61; p <0.001) with better results in masculine type female athletes, except for the "stiffness - sensitivity" factor, which is higher for androgynous type athletes. In addition, the highest reliability was determined among athletes (p <0.001) in 6 factors, and among female athletes in 7 factors. The foregoing indicates that a significant difference in performance corresponds to the possibilities of conducting competitive activities, which affects the formation of the personality of athletes.